EFL Learners' Perceptions of Feedback Types on Oral Tasks: Corrective Feedback vs. Praise. The Case of First-Year Bachelor Students of English at the University of Souk-Ahras. - Rayane TERRAB (My University, 2024)
Abstract The present study investigates EFL students' perceptions of corrective feedback versus praise feedback on oral tasks and their relative effectiveness in enhancing speaking proficiency. It aims to explore how first-year EFL learners at Mohamed-Cherif Messaadia University perceive each feedback type and identify which approach they believe benefits their speaking development more. To achieve these objectives, an exploratory mixed-methods research design involving classroom observation and a students' questionnaire is employed. The study incorporates two research instruments: classroom observation to examine the implementation of corrective and praise feedback during oral activities and a questionnaire to gather students' perceptions and beliefs about the two feedback approaches. The target population consists of 60 first-year EFL learners randomly selected from the entire population. The obtained findings revealed that while both corrective feedback and praise feedback play essential roles in enhancing EFL learners' speaking proficiency, students overwhelmingly perceived praise feedback more positively for its ability to boost confidence, motivation, and active participation in oral tasks. Corrective feedback was acknowledged for its practicality in addressing linguistic inaccuracies. However, praise feedback was viewed as a powerful motivational tool fostering a supportive learning environment conducive to risk-taking and skill development. Based on these results, our hypotheses are confirmed. To this end, several accentuated recommendations are provided for a balanced approach integrating corrective and praise feedback strategies. -------------------- ملخص تبحث هذه الدراسة في تصورات متعلمي اللغة الإنجليزية كلغة أجنبية حول الملاحظات التصحيحية مقابل الملاحظات التشجيعية على المهام الشفوية وفعاليتهما النسبية في تعزيز المهارات الشفوية.كما تهدف إلى استكشاف كيفية إدراك متعلمي السنة الأولى في جامعة محمد الشريف مساعدية لكل نوع من أنواع الملاحظات وتحديد الأسلوب الذي يعتقدون أنه يفيد أكثر في تطوير مهاراتهم الشفوية. لتحقيق هذه الأهداف، تم استخدام تصميم بحث استكشافي متعدد الطرق، يتضمن ملاحظات الفصول الدراسية واستبيانًا للطلبة. تتضمن الدراسة أداتي بحث: ملاحظة الفصل الدراسي لفحص تنفيذ الملاحظات التصحيحية والتشجيعية أثناء الأنشطة الشفوية، واستبيان لجمع تصورات واعتقادات الطلبة حول الأسلوبين. تتكون العينة المستهدفة من 60 متعلمًا للغة الإنجليزية كلغة أجنبية من السنة الأولى، تم اختيارهم بشكل عشوائي. كشفت النتائج المتحصل عليها أن كلا من الملاحظات التصحيحية والتشجيعية تلعبان دورًا أساسيًا في تعزيز المهارات الشفوية لمتعلمي اللغة الإنجليزية كلغة أجنبية، إلا أن الطلبة أبدوا تفضيلًا واضحًا للملاحظات التشجيعية لقدرتها على تعزيز الثقة والتحفيز والمشاركة النشطة في المهام الشفوية. استنادًا إلى هذه النتائج، تم تأكيد فرضياتنا وعلى هذا الأساس،تم تقديم عدد من -------------------- Résumé La présente étude examine les perceptions des apprenants en anglais langue étrangère (EFL) concernant les rétroactions correctives et les encouragements par rapport à leur efficacité relative dans l'amélioration de la compétence en expression orale. Elle vise à explorer comment les étudiants de première année en anglais à l'Université Mohamed-Cherif Messaadia perçoivent chaque type de rétroaction et à identifier quelle approche ils estiment bénéfique pour leur développement oral. Un dispositif de recherche mixte exploratoire est utilisé, impliquant l'observation en classe et un questionnaire. Deux instruments de recherche sont incorporés : l'observation des rétroactions correctives et encouragements lors d'activités orales, et un questionnaire recueillant les perceptions des étudiants sur ces deux approches. La population cible comprend 60 étudiants de première année, sélectionnés aléatoirement. Les résultats ont révélé que bien que les rétroactions correctives et encouragements jouent un rôle essentiel, les étudiants perçoivent de manière écrasante les encouragements comme plus positifs pour renforcer la confiance, la motivation et la participation active. Les rétroactions correctives ont été reconnues pour corriger les inexactitudes linguistiques, mais les encouragements ont été considérés comme un outil motivationnel puissant favorisant un environnement d'apprentissage propice à la prise de risques et au développement des compétences. Sur la base de ces résultats, nos hypothèses sont confirmées. Plusieurs recommandations sont fournies pour une approche équilibrée intégrant les rétroactions correctives et encouragements.